MENELISIK PELAPORAN KEBERLANJUTAN PERUSAHAAN PENERIMA AWARD DI INDONESIA TAHUN 2019 - 2020 - Paulus Tangke (Contemporary Journal on Business and Accounting, 2021)
Purpose – This study aims to investigate the disclosure of GRI Standards in the sustainability reports of national companies receiving awards from the Asia Sustainability Report Rating (ASRRAT) in 2019 and 2020. Design/methodology/approach – Study literature Findings – The results of this study indicate that there are still some standards that are still underreported / disclosed in the sustainability reports of award recipient companies in 2019 and 2020. Originality – This study is a literature study that focuses on reporting the sustainability of companies in Indonesia. Keywords: Standard GRI, Sustainability Report, and Asia Sustainability Report Rating Paper Type Article Text